Neurologists' experiences of participating in the CODES study—A multicentre randomised controlled trial comparing cognitive behavioural therapy vs standardised medical care for dissociative seizures. (October 2019) - Rawlings, Gregg H.; Perdue, Iain; Goldstein, Laura H.; Carson, Alan J.; Stone, Jon; Reuber, Markus
Highlights: Over 80% of doctors asked found it easy to recruit patients to the trial. 90% wanted the treatment pathway developed for the trial to continue. Only 50% could routinely make direct referrals to psychotherapy before / after CODES. Over 85% of doctors reported the CBT package as 'very' or 'extremely' useful. 79% perceived patient satisfaction with the CBT package as 'very good'. Abstract: Purpose: We investigated neurologists' experience of participating in the large CODES trial involving around 900 adults with dissociative seizures which subsequently evaluated the effectiveness of tailored cognitive behavioural therapy (CBT) plus standardised medical care versus standardised medical care alone in 368 patients with dissociative seizures. Method: We asked all neurologists referring patients with dissociative seizures to the CODES study to complete a 43-item online survey. This examined neurologists' (i) demographics, (ii) knowledge of dissociative seizures before and after their involvement in the CODES trial, (iii) clinical practice before, during and since their involvement, and (iv) their experience of the CODES trial. Results: Forty-three (51%) neurologists completed the questionnaire. Only about half of neurologists could make referrals to psychological intervention specific for dissociative seizures before and after the trial. One-third of doctors reported having changed their referral practice following their involvement. The majority (>69%) agreed that patient satisfaction with different aspects of the trial was very high, and 83.7% thought that it was easy to recruit patients for the study. Over 90% agreed they would like the treatment pathway to continue. Respondents found different elements of the trial useful, in particular, the patient factsheet booklet (98%), diagnosis communication advice (93%) and the CBT package (93%). Conclusions: Neurologists participating in CODES generally found it easy to recruit patients and perceived patient satisfaction as very high. However, 46.5% of neurologists could not offer psychotherapy once the trial had finished, suggesting that problems with lack of access to psychological treatment for dissociative seizures persist.